The Impact of Globalization on Dietary Patterns and Health Outcomes (International Journal of Food and Nutritional Sciences, 2022)
Unhealthy dietary patterns have fuelled an epidemic of non-communicable diseases (NCDs) in high-income countries, while rapid dietary transitions in low- and middle-income countries contribute to a spectrum of malnutrition alongside escalating rates of obesity and related NCDs. Economic globalization and trade liberalization are hypothesized as influential factors, yet their precise impact remains contentious. This study presents a rigorous review synthesizing evidence from empirical quantitative studies investigating the relationship between economic globalization processes and nutritional outcomes. By focusing on impact assessment and elucidating underlying mechanisms, the review aims to enhance understanding of the complex interactions shaping dietary patterns and health outcomes worldwide. The findings contribute to ongoing debates by shedding light on the multifaceted pathways through which globalization influences nutritional status, offering insights crucial for devising effective policies and interventions to address the dual burden of malnutrition and NCDs in diverse socioeconomic contexts. The phenomenon of nutrition transition, particularly prevalent in developing countries, underscores the complex interplay between economic development, urbanization, and dietary changes. Moreover, globalization has raised concerns about food safety, quality, and the erosion of traditional dietary practices. Despite these challenges, globalization presents opportunities for promoting healthier dietary habits through initiatives such as food labelling, regulation of marketing practices, and nutrition education. This paper highlights the need for a comprehensive approach to address the health implications of globalization, considering cultural, social, and economic factors to foster healthier diets and improve public health outcomes globally